ONE APPROACH FOR APPLICATION OF GEOGRAPHIC INFORMATION SYSTEMS AND FUZZY LOGIC IN BUSINESS DECISION-MAKING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Computer information systems are applied in all areas of human activity and their main purpose is information analysis and forecasting to make effective and optimal management decisions. Geographic Information Systems (GIS) are modern computer information systems for processing, mapping, and analyzing geospatial information. The creation of new projects in a GIS environment to support management decisions could be combined with artificial intelligence technologies such as fuzzy logic, so that different dimensional input geographic and business parameters can automate to some extent some logically based management decisions. This report explores the possibilities of fuzzy logic technologies to process geographic and statistical economic data for making adequate business decisions. Data on localities, distances to a specific site, demographic profile of the population and historical sales reference for a given region were used to generate output variable values for frequency of advertising campaigns, selection of product range and logistics parameters. The environment for developing the Fuzzy inference system is Matlab, and the software for the geographic information system is ArcView.